Crystallization Properties of Al-Sb Alloys for Phase Change Memory Applications. (23rd July 2021) - Ume, Rubab; Gong, Haibo; Tokranov, Vadim; Yakimov, Michael; Sadana, Devendra; Brew, Kevin; Cohen, Guy; Lavoie, Christian; Schujman, Sandra; Beckmann, Karsten; Cady, Nathaniel; Oktyabrsky, Serge
Abstract : Material properties of Al-Sb binary alloy thin films deposited under ultra-high vacuum conditions were studied for multi-level phase change memory applications. Crystallization of this alloy was shown to occur in the temperature range of 180 °C–280 °C, with activation energy >2 eV. X-ray diffraction (XRD) from annealed alloy films indicates the formation of two crystalline phases, (i) an Al-doped A7 antimony phase, and (ii) a stable cubic AlSb phase. In-situ XRD analysis of these films show the AlSb phase crystalizes at a much higher temperature as compared to the A7 phase after annealing of the film to 650 °C. Mushroom cell structures formed with Al-Sb alloys on 120 nm TiN heater show a phase change material resistance switching behavior with reset/set resistance ratio >1000 under pulse measurements. TEM and in situ synchrotron XRD studies indicate fine nucleation grain sizes of ∼8–10 nm, and low elemental redistribution that is useful for improving reliability of the devices. These results indicate that Te-free Al-Sb binary alloys are possible candidates for analog PCM applications.